2010
DOI: 10.1002/pits.20471
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between peer victimization and post‐traumatic stress symptomatology in a rural sample

Abstract: Peer victimization (PV) has been associated with a number of negative psychological sequelae. Few studies, however, have examined the relationship between PV and the symptomatology of posttraumatic stress disorder, and no studies to date have examined this relationship in a rural sample. Adapted versions of the SEQ-SR and the TSCC were used to assess the relationship between PV and post-traumatic stress symptomatology in a sample of 244 rural youths (ages 10-14) in two school districts in a south-central area … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
26
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 31 publications
5
26
0
2
Order By: Relevance
“…This result reinforces data from studies that argue that school victims may also develop PTSD symptoms (Crosby et al, 2010;Idsoe et al, 2012;Storch & Esposito, 2003). In the PTSD literature, in general, albeit not specific on school violence, there are prevalence studies that may be useful to compare with the present data.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…This result reinforces data from studies that argue that school victims may also develop PTSD symptoms (Crosby et al, 2010;Idsoe et al, 2012;Storch & Esposito, 2003). In the PTSD literature, in general, albeit not specific on school violence, there are prevalence studies that may be useful to compare with the present data.…”
Section: Discussionsupporting
confidence: 85%
“…Besides the commonly described symptoms, the literature has shown that individuals victimized by peers may also develop Post-Traumatic Stress Disorder symptoms (PTSD) (Albuquerque, Williams, & D'Affonseca, 2013;Crosby, Oehler, & Capaccioli, 2010;Idsoe et al, 2012;Storch & Esposito, 2003). However, there are few studies clarifying how the relationship between these two variables occurs (Idsoe et al, 2012;McKenney, Pepler, Craig, & Connoly, 2005;Mynard, Joseph, & Alexander, 2000).…”
Section: Impacto De Las Peores Experiencias En La Escuela En Estudianmentioning
confidence: 99%
See 1 more Smart Citation
“…Dos participantes que sofreram um evento traumático, 25% relataram ter sofrido humilhação ou bullying durante a infância. Crosby et al (2010) realizaram uma pesquisa com 244 estudantes, com idades entre 10 a 14 anos, de três escolas rurais dos Estados Unidos. Os autores buscaram dar suporte à hipótese de que a vitimização por pares/bullying pode estar associada a sintomas de TEPT.…”
Section: Resultsunclassified
“…Além disso, as pesquisas que relacionam bullying a sintomas de TEPT (Crosby et al, 2010;Mynard et al 2000;Storch & Esposito, 2003) indicaram correlações positivas e significativas entre os dois fenômenos, demonstrando que, a curto prazo, ser vítima de bullying pode levar ao aparecimento de sintomas de TEPT. Cabe destacar que, tanto Storch e Esposito (2003), quanto Mynard et al (2000), afirmam que, apesar do aumento do número de pesquisas que investiguem as interações negativas entre pares, poucos estudos examinam a relação entre as consequências psicológicas dessas interações.…”
Section: Resultsunclassified